2017
DOI: 10.1017/aer.2016.122
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the fatal 1985 Manchester Airport B737 fire

Abstract: In this paper, fire and evacuation computer simulations are used to reconstruct the 1985 Manchester Airport B737 fire that resulted in the loss of 55 lives. First the actual fire and evacuation are reconstructed. Secondly, the impact of exit opening times and external wind on the fire and evacuation are investigated. Finally, the potential benefit offered by modern materials is evaluated. The results suggest that the number of fatalities could have been reduced by 87% had the forward right exit not malfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…To sum up, it can be said that the highest possible survival rate for passengers and crew in air accidents is due to constantly improving regulations in the area of airworthiness and operational requirements, improving aircraft design in the area of emergency evacuation systems and their technical reliability, and due to constantly improving procedures and training for flight crew and on-board personnel. How important it is for the smooth implementation of evacuation procedures can be confirmed by the "Fire Safety Engineering Group" (FSEG) at the Univeristy of Greenwich, published in January 2017, which concerns an analysis of the Manchester accident of August 22, 1985, by Boeing 737-200 operated by British Airtours [16]. The analysis of the accident and the simulations carried out showed that: one minute's delay in opening the aircraft's front escape door resulted in the death of 48 passengers, while a 30-second delay in opening the escape door to the aircraft wing resulted in the death of 20 passengers.…”
Section: Wybrane Zagadnienia Ewakuacji Samolotów Pasażerskichmentioning
confidence: 99%
See 1 more Smart Citation
“…To sum up, it can be said that the highest possible survival rate for passengers and crew in air accidents is due to constantly improving regulations in the area of airworthiness and operational requirements, improving aircraft design in the area of emergency evacuation systems and their technical reliability, and due to constantly improving procedures and training for flight crew and on-board personnel. How important it is for the smooth implementation of evacuation procedures can be confirmed by the "Fire Safety Engineering Group" (FSEG) at the Univeristy of Greenwich, published in January 2017, which concerns an analysis of the Manchester accident of August 22, 1985, by Boeing 737-200 operated by British Airtours [16]. The analysis of the accident and the simulations carried out showed that: one minute's delay in opening the aircraft's front escape door resulted in the death of 48 passengers, while a 30-second delay in opening the escape door to the aircraft wing resulted in the death of 20 passengers.…”
Section: Wybrane Zagadnienia Ewakuacji Samolotów Pasażerskichmentioning
confidence: 99%
“…The analysis of the accident and the simulations carried out showed that: one minute's delay in opening the aircraft's front escape door resulted in the death of 48 passengers, while a 30-second delay in opening the escape door to the aircraft wing resulted in the death of 20 passengers. If all emergency exits had been opened at the time set in the certification tests, all passengers and crew would have been effectively evacuated [16].…”
Section: Wybrane Zagadnienia Ewakuacji Samolotów Pasażerskichmentioning
confidence: 99%
“…(4) A seek curve is generated to define his desired motion. (5) The occupant attempts to move along the tangent to his current seek curve.…”
Section: Path Generationmentioning
confidence: 99%
“…On February 5, 2015, a fire accident happened in Yiwu Mall in Huidong County, Guangdong Province of China, which resulted in 17 people dying in the cinema on the fourth floor. Some more accidents can be found in Prager et al 4 and Galea et al 5 When accidents happen, improving the pedestrian flow rates at those bottlenecks on the evacuation routes to make sure most of the occupants can be evacuated in time can decrease the losses of life and property obviously, and this issue attracted lots of attention during the past several decades. For example, by doing some simulations by computer, Helbing et al 6 demonstrated the escape rate of crowds under panic conditions is enhanced if an obstacle is asymmetrically placed on the upstream side of an narrow exit.…”
Section: Introductionmentioning
confidence: 99%
“…This does not necessarily reduce the thermal degradation of materials within the compartment, as the hot gas mixture present has enough energy to allow the endothermic pyrolysis to continue. An investigation into the 1985 British Airtours fight 28M using modern Computational Fluid Dyanmics (CFD)-based analysis concluded that a delay of 50 s in fire propagation could have saved all 55 lives lost in the disaster [16]. This further emphasises the destructive nature of fire within a compartment when considering that the ignition position was outside of the cabin, and local to the engine.…”
Section: Literature Reviewmentioning
confidence: 99%